Factors associated with cesarean delivery in adult nulliparous women (Acta Scientiarum. Health Sciences, 2021)
The aim of this study was to analyze the sociodemographic factors associated with cesarean section in adult women with conditions favorable for normal delivery and to identify the groups most likely to undergo this surgery in the state of Santa Catarina (SC). A case control study with microdata from the Sistema de Informação de Nascidos Vivos on 7,065 women for 2016 in SC. A relationship between cesarean section and sociodemographic variables was analyzed by logistic regression where we calculated the Adjusted Odds Ratio (AOR), confidence interval and p-value. The probability of cesarean section for each group of women (called "interaction") was also calculated. Among women with more favorable conditions for normal childbirth, the prevalence of cesarean section was 41.1%. Lower chance of cesarean section was found for women without partners (AOR: 0.79 [0.71-0.87]), up to 8 years of schooling (AOR: 0.56 [0.47-0.66]), with up to 2 prenatal visits (AOR: 0.46 [0.23-0.90]). The most likely group of women (51.4% [49.3-53.4]) to undergo cesarean section are women who perform 7 to 15 prenatal visits and have 12 or more years of schooling. A cesarean section occurs with women who have greater access to education and prenatal care and those who have partners, even though the aspects favor normal childbirth, suggesting that this does not seem to be a decision only by women.